PENGARUH PASSING STATIS DAN DINAMIS TERHADAP PENERIMAAN BOLA PERTAMA SEPAK TAKRAW SMK N 3 SEMARANG - Rosyanto, Viki Ardi; Pratama, Dani Slamet (YLPK Mahardhika, 2024)
This study aims to investigate the influence and differences between static and dynamic passingexercises in receiving the first ball. The research method uses the M-S (Matched Subject Design) standard. The total population is 15 students and the sample is 12 students, using the purposive sampling technique. The research instrument with the first ball acceptance test was retested with validity of 0.79 and reliability of 0.96. The independent variable is the practice of static and dynamic passing, the dependent variable is the ability to receive the first ball. Data analysis used the t-test statistic at a significance level of 5% with d.b n-1. The results of the research were: 1) The t-score of experimental group 1 was higher than the t-table (5.869 > 2.571) which means that there was an influence from static passingtraining. 2) The t-score of experimental group 2 is higher than the t table (6.932 > 2.571) which means that there is an influence from dynamic passingtraining. 3) the test results for the difference between the T-score of static and dynamic passingexercises is smaller than the T-Table (0.209<2.571), which means there is no difference in influence.